Biofilm aggregates and the host airway-microbial interface - Hall-Stoodley, Luanne; McCoy, Karen S. (Frontiers in Cellular and Infection Microbiology, 2022)
Biofilms are multicellular microbial aggregates that can be associated with host mucosal epithelia in the airway, gut, and genitourinary tract. The host environment plays a critical role in the establishment of these microbial communities in both health and disease. These host mucosal microenvironments however are distinct histologically, functionally, and regarding nutrient availability. This review discusses the specific mucosal epithelial microenvironments lining the airway, focusing on: i) biofilms in the human respiratory tract and the unique airway microenvironments that make it exquisitely suited to defend against infection, and ii) how airway pathophysiology and dysfunctional barrier/clearance mechanisms due to genetic mutations, damage, and inflammation contribute to biofilm infections. The host cellular responses to infection that contribute to resolution or exacerbation, and insights about evaluating and therapeutically targeting airway-associated biofilm infections are briefly discussed. Since so many studies have focused on Pseudomonas aeruginosa in the context of cystic fibrosis (CF) or on Haemophilus influenzae in the context of upper and lower respiratory diseases, these bacteria are used as examples. However, there are notable differences in diseased airway microenvironments and the unique pathophysiology specific to the bacterial pathogens themselves.